KONSTITUSIONALITAS DEKRIT PRESIDEN 5 JULI 1959 DAN MAKLUMAT PRESIDEN 23 JULI 2001 - Changnata, Neysa; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In 1959, Homeland was in an emergency, In order to restore politicalstability at that time, then President Soekarno took firm step to issue a decreewich contains the return to the Constitution of 1945, dissolved the ConstituentAssembly, and forming MPRS and DPAS. This decree then could be implementedbecause of the support of the military, and the people of Indonesia, and then thisdecree was added to the state No. sheet 75 of 1959 and become decision of thePresident No. 150.On 30 April 2001, the House of Representatives of the Republic of Indonesiathe Plenary Meeting have dropped Memorandum II as outlined in the Decision ofthe Board of Representatives of the Republic of Indonesia No. 47 / IV / 2000-2001dated 30 April 2001 to President Abdurrahman Wahid which states that 1) thePresident has violated the Guidelines of State Policy (Guidelines), 2) Within 3(three) months, the President does not regard Memorandum, and 3) Provide 1(one) month to the President to respond to the Memorandum.Escalation of the conflict increased when President Abdurrahman Wahid onJuly 23, 2001 at 1:10 pm President of the Republic of Indonesia edict establishesthat contains clotting Indonesian People's Consultative Assembly and the Houseof Representatives of the Republic of Indonesia, to restore sovereignty to thepeople, as well as to take action and prepare bodies required to hold electionswithin a year, saving a total reform movement of the barrier elements of NewOrder to freeze the Golkar Party's decision to wait for the Supreme Court of theRepublic of Indonesia. Furthermore, the Supreme Court of the Republic ofIndonesia on July 23, 2001 issued a legal considerations which contains theconsideration that the edict of President contrary to law.The legal writing was prepared by the author through a normative juridicalanalysis based one through a historical approach which seeks to assess the edictof President July 23, 2001 from the perspective of Constitutional Law, which isbased on the research results that the edict of President July 23, 2001 a subjectiveemergency laws or unwritten (Ongeschreven Staatsnoodrecht), because the realityis not found in the Indonesian constitution or not a written rule. As far as thescientific study was conducted by the authors, the controversy notices PresidentJuly 23, 2001 is actually a form of resistance against President AbdurrahmanWahid political dynamics that exist in the House of Representatives of theRepublic of Indonesia and the People's Consultative Assembly of the Republic ofIndonesia.Keywords : -The Presidential Decree and Intimation -Subjective Emergency-The Political Dynamics